2018
DOI: 10.3168/jds.2017-14350
|View full text |Cite
|
Sign up to set email alerts
|

Total replacement of corn silage with sorghum silage improves milk fatty acid profile and antioxidant capacity of Holstein dairy cows

Abstract: Total mixed rations containing corn silage (CS) or forage sorghum silage (SS) were fed to mid-lactation Holstein cows to determine the effects on feed intake, lactation performance, milk composition and fatty acid profile, nutrient digestibility, blood metabolites, rumen microbial N synthesis, and antioxidant status. The experiment was designed as a 2-period changeover (two 28-d periods) trial with 2 diets including CS diet or SS diet and 12 cows. Total replacement of CS with SS had no significant influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
2
18
1
2
Order By: Relevance
“…Furthermore, MCP and the efficiency of microbial protein synthesis (EMPS) were different among treatments, and higher values were found in the groups supplemented with FTMR that contained 2% sulfur and was ensiled for 7 day, while the lowest was found in the non-ensiling FTMR diet ( p < 0.01). Similarly, Khosravi et al [36] revealed that an ensiling time could increase the rate of nonstructural carbohydrate degradation, which could supply a substrate for microorganism growth [37]. It can also be noted that the microorganisms in the rumen synthesize sulfur containing amino acids and aid in the production of MCP.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, MCP and the efficiency of microbial protein synthesis (EMPS) were different among treatments, and higher values were found in the groups supplemented with FTMR that contained 2% sulfur and was ensiled for 7 day, while the lowest was found in the non-ensiling FTMR diet ( p < 0.01). Similarly, Khosravi et al [36] revealed that an ensiling time could increase the rate of nonstructural carbohydrate degradation, which could supply a substrate for microorganism growth [37]. It can also be noted that the microorganisms in the rumen synthesize sulfur containing amino acids and aid in the production of MCP.…”
Section: Resultsmentioning
confidence: 99%
“…This relationship has been investigated in in vitro studies comparing the effect of various sources of sulfur on the bacterial synthesis, the utilization of NH 3 -N, and nutrient digestion over a 96-h incubation period [37]. It can also be noted that sulfur addition increases the performance of microbial protein synthesis to production of MCP and improves the amino acid balance [38].…”
Section: Rumen Characteristics and Blood Profilesmentioning
confidence: 99%
“…Several studies aimed to completely replace corn with sorghum silage in dairy cow's diet have been conducted with contrasting results. Indeed, milk yields were unaffected by treatment according to Miron et al [21] and Khosravi et al [23], while Colombini et al [3] and Cattani et al [1] reported higher milk yield when cows received the diet based on corn silage. This negative results for sorghum silage could be attributed to the variety of forage, in fact, Grant et al [17] found negative influence of replacing corn with sorghum silage sorghum only when dairy cows were fed diet based on non-BMR sorghum while milk yield was unaffected when BMR was used.…”
Section: Discussionmentioning
confidence: 95%
“…Higher proportion of linoleic acid we have found also in corn silage than in sorghum silage, which instead showed higher percentage of alfa-linolenic acids. Cattani et al [1] found either linoleic and alfa-linolenic acids higher in milk when cows were fed corn compared to sorghum silage; on the contrary Khosravi et al [23] reported higher proportions of alfa-linolenic acid in milk of dairy cows fed sorghum silage diet. Both linoleic and alfa-linolenic acids are recognised as main precursors of milk CLA [13,27] which in present trial was unaffected by the treatment in contrast with Cattani et al [1] which reported higher total CLA when cows were fed sorghum silage.…”
Section: Discussionmentioning
confidence: 96%